Islanding Detection Algorithm Based on Adaptive Voltage Positive Feedback - Jihong Zhang; Zhenkui Wu; Hua Li; Hanshan L I; Yongfeng Ren (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Islanding detection is an essential function of the grid-connected inverter of distributed power generation system. The deficiency of traditional islanding detection methods should be given due importance, especially the phenomena such as islanding detection failure when the output power of the inverter balances with the load power, and the use of active frequency and phase shifting method affecting the quality of power. In this regard, an improved islanding detection method based on adaptive voltage positive feedback was proposed. A mathematical model was established, and the hardware circuit was tested. The constraint conditions on the success of islanding detection and the pattern of voltage variation at the point of common coupling before and after incorporation to the grid were studied. The simulation result shows that this method has the advantages of high detection speed, small blind area and high reliability. The index requirements specified in IEEE Std.2000-929 are met. The reasonability of the proposed scheme is verified. DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.5475